2021
DOI: 10.12998/wjcc.v9.i9.2077
|View full text |Cite
|
Sign up to set email alerts
|

Expert consensus on the diagnosis and treatment of myofascial pain syndrome

Abstract: Myofascial pain syndrome (MPS) is characterized by myofascial trigger points and fascial constrictions. At present, domestic and foreign scholars have not reached a consensus on the etiology and pathogenesis of MPS. Due to the lack of specific laboratory indicators and imaging evidence, there is no unified diagnostic criteria for MPS, making it easy to confuse with other diseases. The Chinese Association for the Study of Pain organized domestic experts to formulate this Chinese Pain Specialist Consensus on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 55 publications
0
35
0
1
Order By: Relevance
“…An appropriate diagnosis and rehabilitation of the neuropathic pain component plays an important role in the treatment of MPS. Therefore, it is important to consider the neuropathic component in the management of MPS (2,(22)(23)(24). In this study, we aimed to evaluate the neuropathic pain component in patients with myofascial pain syndrome by using DN4 scale, and to examine the effects of neuropathic pain on emotional status, sleep and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…An appropriate diagnosis and rehabilitation of the neuropathic pain component plays an important role in the treatment of MPS. Therefore, it is important to consider the neuropathic component in the management of MPS (2,(22)(23)(24). In this study, we aimed to evaluate the neuropathic pain component in patients with myofascial pain syndrome by using DN4 scale, and to examine the effects of neuropathic pain on emotional status, sleep and quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Variation in the method of cupping technique may have played a role in the difference in effectiveness in the studies. However, the guidelines revealed a good level of evidence for therapeutic exercises in rehabilitation treatment (36,37). Several studies showed the influence of manual therapy on trapezius, neck, and shoulder myofascial pain reduction (38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Myofascial pain syndrome (MPS) is the most commonly diagnosed musculoskeletal condition (1). Poor posture is the primary cause of MPS (1).…”
Section: Introductionmentioning
confidence: 99%